A proposed technique for simulating the complete electric drive systems with a complex kinematics chain - Erdogan, Nuh; Hena, Humberto; Grisel, Richard (IEEE, 2007)
This study concerns the simulation of industrial systems where the configuration is composed of electrical machine-converter-kinematics chain and a mechanical load. A simulation technique is proposed for transient studies of the complete electric drive systems (EDS). This technique is based on integrating two different tools where each part of the drive system is simulated. The integration of the simulators is performed by co-simulation. Tools in Matlab (R)/SIMLTLINK (R) are used to implement and simulate the electric parts of EDS. Matlab (R)/SIMULINK (R) can be interfaced by means of Co-simulation with the ITI (R)-SIM simulator which is selected for the mechanical part simulation. As experimental study, an industrial EDS having a complex kinematics chain with a mechanical load have been used. Simulated and experimental results have been presented and found to be in very good correlation. In conclusion, the obtained results are evaluated to prove the performance of the proposed technique.
Keywords: dynamic simulation; co-simulation; electric drive system; kinematics chain; Automation & Control Systems; Engineering; Transportation